Consecuencias del valor razonable al implementar las NIIF en los indicadores financieros del sector cooperativo de Boyacá. Estudio de casos (2021)
The main goal of this article is to present the result to evaluate how the financial conditions of the cooperatives in Boyacá (Colombia), were concerned by the transition of accounting system model, influenced by the model defined by the decree 2649 ruled by the principles of accounting generally accepted in Colombia (COLGAAP) of 1990, to the standards of financial information defined in the law 1314 (NIIF), this Project was made through the comparisson between the financial situation state of a sample of the cooperatives found in group II, defined in the law 1314 of 2009, for the years 2014, with the financial situation state of 2016, the relation between the indicators of financial performance in each term was analyzed, the impact in the financial indicators measured through the model Z of Edward Altman was used to get the final result where is shown the conditions of the bankruptcy possibilities of some cooperatives in the next five years, impact that would be mainly justified by applying the fair market value to some counts of the financial states analyzed.